Determinación de los niveles sonoros en actividades sociales y su influencia en la salud de la población de la ciudad de Tarapoto, provincia de San Martín - Rios Pérez, Bruno Ulises (2014)
This researcb woik entitled "DETERMINATION OF NOISE LEVELS IN SOCIAL ACTIVITIES AND HEALTH IFLUENCIA POPULATION TARAPOTO CITY, PROVIN€E (:)F SAN MAR'fiN, SAN MAR'fiN REGION 2014". It was developed in the city of Tarapoto, airning to determine noise levels in social activities and their influence on the health ofthe population ofthe city ofTarapoto. The research is descriptive, it was sarnpled six (6) rnonitoring points located at strategic points in the city, randornly selected in the rnain assernbly points and hours 6:30 to 7:30 a.m., 12:00 - 1:00 prn, 5:30 to 6:30 prn. The rnan then went to the following conclusions: It has been possible to determine the sound Ievels generated in the City of Tarapoto ranging between 89.3 and 96.5 dB, which exceed the Environrnental Quality StandardsECAs established in the DS No. 085-2003 PC, it was determined that the Monitoring Point No. 02, which corresponds to the Fun Center Antiqua Disco Club- The Rustic. which is located on the outskirts of the city of "farapoto a few rneters of the Fire Departrnent of Peru, where bornes and businesses (rnixed area - residential - cornrnercial) is observed, witb houses Iocated between 50 to 100 rneters around the rnost affected; and the situation of people living bornes are is delicate and that their health and well-being and welfare are severely cornprornised because of the high noise levels of social activities are generating, but also all basic activities are affected, cornrnunication between people, not only frorn a social point ofview and respect, but in terms of cornrnercial activity since in these avenues settle irnportant and nurnerous shops.